Satisfaction analysis of traditional retail market and modern retail market in Pekanbaru (Case study : in district Payung Sekaki) - Mita Jayanti; Jushermi '; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the District Payung Sekaki Pekanbaru is On Traditional Retail Market; Retail Market Labuh Baru and Retail Modern Cendana Mart. To determine differences in the level of satisfaction of consumers shopping mix dimensions and Traditional Retail Market Retail Market Simplified. The benefits of this research can be valuable for retailers enter to be able to know the attributes or indicators that should be included into the correct quadrant.This study uses primary data and secondary data. Technique where data collection is done by questionnaire method. The study population are housewives who shop at traditional retail markets and modern retail market in the District Payung Sekaki. By using formulation Slovin and Classified Random Sampling techniques, sample obtained number of 100 respondents were divided into two. 50 respondents to the traditional retail market and 50 respondents to the modern retail market. Technical analysis of the data was done descriptively by doing a comparison between the value of the average (mean) level of expectations of the respondents with an average rating of perceived service performance levels based on the results of research and using matrix Importance Performance Analysis (IPA).Based on the results we concluded that coordinates the average score on the level of performance and expectations of the modern retail market and traditional retail markets respectively, are 3.63 and 4.49 for the modern retail market, 3.69 and 4.49 for the traditional retail market .Keywords: Level of Satisfaction and Retail